Variation in “biodiversity value” of peatmoss species in Sphagnum section Acutifolia (Sphagnaceae) - Shaw, A. J. (2014)
Species are the most common currency by which biodiversity is measured, but species are not equivalent in ‘‘biodiversity value’’ because of differences in phylogenetic history and current population processes. Morphologically defined species in Sphagnum section Acutifolia (Bryophyta) were compared with regard to how phylogenetically distinct each is from its sister species and how much nucleotide variation each encompasses. Comparisons were based on sequence variation at seven nuclear and chloroplast loci. Assignment of collections to morphospecies accounted for about 57–75% of the overall nucleotide variation at the seven loci, but morphospecies differed greatly in how much nucleotide diversity they encompass. In addition, morphospecies varied widely in their genetic distinctiveness, estimated as the length of the stem branch from the most recent common ancestor and numbers of differentially fixed and shared polymorphic nucleotides among taxa. Levels of molecular diversity within morphospecies were not correlated with their degree of isolation. Factors that affected the biodiversity value of species include age, mode of origin, demographic history, and reproductive biology.